(untitled) (Circe de clásicos y modernos, 2026)
The modes of poetic composition have been represented in Greek literature in diverse ways since the Homeric epic. This article traces and analyzes some dominant ideas about the productive task of the comic poet in the work of Aristophanes, especially in the parabasis, and determines that they describe a vision of the playwright conceived as an agent, with a high degree of autonomy from extrahuman conditioning, capable of original productions endowed with a political function, perspective of the poet’s activity that represents a partial break with traditional representations.